Biodiversity associated to European sheep grazed pastures - Rosa García R.; Peric T.; Cadavez V.; Ko N.; Lima Cerqueira J.; Pietro Stanganello R.; Fernandes E.; Celaya R.; Gonzales-Barrón Ú.; Baratta M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
We analysed the biodiversity of foliage arthropods in nine sheep grazed pasturelands in five European countries. During the maximum flowering period in 2018, entomofauna was collected in 4-6 areas within each pasture, performing 6 transects/area and 25 sweeps per transect. Multivariate analyses tested the differences in total arthropod community composition among degrees of intensification, bioregions and types of pastures. A total of 51,474 arthropods from 3 classes, 17 orders and 95 taxonomical groups were recorded. Univariate analyses revealed that total arthropod abundance was higher in extensive than in intensive systems (P<0.01). It also differed between bioregions (higher in Alpine than in Continental, P<0.05) and between types of pastures (higher in mountain than in lowland pastures where animals are supplemented, P<0.05). Total taxa richness was not influenced by any of the three factors. However, multivariate analyses indicated that community composition differed among intensive and extensive systems, bioregions and types of pastures (P<0.001). The greatest differences occurred between Alpine and Mediterranean (P<0.001), and Mediterranean and Continental pastures (P<0.05), as well as between lowland seminatural and improved pastures (P<0.05), and seminatural and mountain pastures (P<0.001). These results reveal the complex and varied communities associated to the diverse sheep systems and valorise the role of the more extensive, mountain and natural pastures for the conservation of biodiversity in sheep grazed areas.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)